2000
DOI: 10.1128/mcb.20.19.7401-7409.2000
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Repression by Drosophila Methyl-CpG-Binding Proteins

Abstract: In vertebrates, including the mammals, the chromosomal DNAs are modified by C methylation at a limited number of CpG dinucleotides, resulting in m 5 CpG, methylated at position 5 of the C residues. This methylation at CpG has been implicated in the regulation of a number of genetic activities during mammalian cell differentiation and embryo development. These activities include tissue-specific gene transcription, X chromosome inactivation, genomic imprinting, cellular defense against viral agents, and tumorige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 35 publications
1
53
0
Order By: Relevance
“…Two previous studies have failed to detect an interaction between MBD2/3 and CpG-methylated probes (Ballestar et al, 2001;Tweedie et al, 1999). A third study described a preferential binding of the short MBD2/3 isoform to a human DNA probe containing a single methylated CpG (Roder et al, 2000). However, the short isoform lacks parts of the methyl-DNA binding domain, which rendered the significance of this finding unclear.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Two previous studies have failed to detect an interaction between MBD2/3 and CpG-methylated probes (Ballestar et al, 2001;Tweedie et al, 1999). A third study described a preferential binding of the short MBD2/3 isoform to a human DNA probe containing a single methylated CpG (Roder et al, 2000). However, the short isoform lacks parts of the methyl-DNA binding domain, which rendered the significance of this finding unclear.…”
Section: Resultsmentioning
confidence: 78%
“…Confocal analysis of mutant embryos showed local displacement of MI-2 from DNA and indicated that MBD2/3 is associated CpG binding domain of MBD2/3 contains a number of deviations from the consensus MBD that seemed to be incompatible with a standard methyl-CpG binding activity (Ballestar et al, 2001;Tweedie et al, 1999). A very weak association with a CpG-methylated DNA fragment could be demonstrated in other experiments, but this interaction was observed with the short isoform and therefore seemed to be independent of the full-length methyl-CpG binding domain (Roder et al, 2000). Together, these results suggested that MBD2/3 might represent a functional homologue of mammalian MBD3, rather than MBD2 (Ballestar et al, 2001;Tweedie et al, 1999).…”
Section: Introductionmentioning
confidence: 88%
“…S. cerevisiae, C. elegans) has long raised questions about the importance of DNA methylation for gene control in eukaryotes. Interestingly, while Drosophila was long thought not to have DNA methylation, recent reports have identi®ed genes with homology to the vertebrate DNA methylation machinery (Tweedie et al, 1999;Hung et al, 1999;Roder et al, 2000;Lyko et al, 2000a). In addition, trace amounts of cytosine methylation have been detected in this organism (Gowher et al, 2000;Lyko et al, 2000b).…”
Section: Chromatin and Transcriptionmentioning
confidence: 99%
“…The dMBD2/3 protein was shown to have the capacity to bind to CpG-methylated DNA, at least in vitro. 16,17 In the year 2000, Lyko et al reported that Drosophila DNA is methylated, but that Drosophila genome methylation is restricted to early stages of embryo development. 18 Confocal analysis of immunostained Drosophila embryos provided further evidence for the methylation of embryonic DNA.…”
Section: Dna Methylation In Insectsmentioning
confidence: 99%